2022
DOI: 10.1155/2022/8745722
|View full text |Cite|
|
Sign up to set email alerts
|

Candidate Genes of Allergic Dermatitis Are Associated with Immune Response

Abstract: Allergic dermatitis (AD) is a common and burdensome inflammatory skin disease, and diagnosis is challenging. This study was conducted to identify candidate genes for AD diagnosis and underlying molecular mechanisms. Gene expression profiles were obtained from datasets GSE121212, GSE130588, and GSE157194. Use differential analysis to identify differentially expressed genes (DEGs) between AD and control. Use enrichment analysis to identify potential molecular dysregulation mechanisms. Comprehensive least absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Journal of Healthcare Engineering has retracted the article titled "Candidate Genes of Allergic Dermatitis Are Associated with Immune Response" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Healthcare Engineering has retracted the article titled "Candidate Genes of Allergic Dermatitis Are Associated with Immune Response" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Candidate Genes of Allergic Dermatitis Are Associated with Immune Response” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%